2017
DOI: 10.4172/2157-7099.1000483
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Metastases from a Small Cell Lung Carcinoma: A Case Report

Abstract: BackgroundSmall cell lung carcinomas (SCLC) represent almost 20-25% of all bronchogenic carcinoma and constitutes a group of tumors with high potential of metastases at the time of diagnosis [1,2]. The pancreas is an uncommon site of secondary localization from this neoplasm [3]. Limited data are available concerning incidence, clinical picture, management and prognosis for pancreatic metastases of small cell lung carcinoma. In this paper, we report a case of documented pancreatic involvement due to small cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…4 One study reported that almost 94% cancer patients diagnosed with one or more abnormal coagulation functions, especially it gets more worse in terminal stage metastasis patients. 5,6 Lung cancer patients also suffer from hypercoagulation, hyperfibrinolysis, thrombosis and abnormal tumour growth which further contribute in tumour development. 7 Previous relevant studies have the following arguments that correlate NSCLC progression and coagulation function changes, the fibrin has high molecular weight in the plasma part and increase amount of fibrin in NSCLC are more prone to hypercoagulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 One study reported that almost 94% cancer patients diagnosed with one or more abnormal coagulation functions, especially it gets more worse in terminal stage metastasis patients. 5,6 Lung cancer patients also suffer from hypercoagulation, hyperfibrinolysis, thrombosis and abnormal tumour growth which further contribute in tumour development. 7 Previous relevant studies have the following arguments that correlate NSCLC progression and coagulation function changes, the fibrin has high molecular weight in the plasma part and increase amount of fibrin in NSCLC are more prone to hypercoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that almost 94% cancer patients diagnosed with one or more abnormal coagulation functions, especially it gets more worse in terminal stage metastasis patients 5,6 . Lung cancer patients also suffer from hypercoagulation, hyperfibrinolysis, thrombosis and abnormal tumour growth which further contribute in tumour development 7…”
Section: Introductionmentioning
confidence: 99%